Massive unseen companions to hot faint underluminous stars from SDSS (MUCHFUSS): Analysis of seven close subdwarf B binaries - Geier, Stephan; Maxted, P. F. L.; Napiwotzki, R.; Ostensen, R. H.; Heber, Ulrich; Hirsch, H.; Kupfer, Thomas; Mueller, S.; Tillich, A.; Barlow, B. N.; Oreiro, R.; Ottosen, T. A.; et al. (Astronomy & Astrophysics, 2011)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions like massive white dwarfs (M > 1.0 M⊙), neutron stars or stellar mass black holes. The existence of such systems is predicted by binary evolution theory and recent discoveries indicate that they exist in our Galaxy. First results are presented for seven close binary sdBs with short orbital periods ranging from ≃ 0.21 d to 1.5 d. The atmospheric parameters of all objects are compatible with core helium-burning stars. The companions are most likely white dwarfs. In one case the companion could be shown to be a white dwarf by the absence of light-curve variations. However, in most cases late type main sequence stars cannot be firmly excluded. Comparing our small sample with the known population of close sdB binaries we show that our target selection method aiming at massive companions is efficient. The minimum companion masses of all binaries in our sample are high compared to the reference sample of known sdB binaries. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: binaries: close; binaries: spectroscopic; subdwarfs; white dwarfs